Discriminación étnica en el trabajo : El caso de los albañiles en Otavalo - Flores Ruales, Luis Alberto (2018)
Ethnic discrimination against indigenous people is part of the colonial matrix that expresses itself in new forms and in different spheres and strata of society. A latent case of ethnic discrimination is that of the construction workers in Otavalo city, who due to their ethnic and economic condition are victims of discrimination. This research seeks to understand how discriminatory imaginaries are constructed and developed around the indigenous masons of Otavalo, who move from rural areas to the city, in search of work; this entails a cultural conflict, which forces him to redefine himself socially and look for new strategies to adapt to a new context of interaction in urbanity. From the techniques of: participant observation, discourse analysis, surveys, in-depth interviews and life stories; it seeks to highlight from the theory of imaginaries, the daily dynamics in the work of the indigenous mason, within the city of Otavalo and identify specific cases of ethnic discrimination that arise around the indigenous mason of Otavalo, who comes to the city from the rural, looking for work.